Atomically Surficial Modulation in Two-Dimensional Semiconductor Nanocrystals for Selective Photocatalytic Reactions - Zhu, Shuwen; Li, Xinyuan; Zhang, Jiatao (Frontiers in Chemistry, 2022)
Photocatalysis, directly converting solar energy into chemical energy, is identified as an ideal strategy to release the increasing consumption of fossil fuel and facilitate carbon neutralization. In the last few years, a great number of endeavors have been devoted to develop photocatalysts with high conversion efficiency and selectivity. Atomically surficial modulation strategies, including surface vacancies, single-atom modification, and dual sites components, exhibited positive impacts on tuning key steps of photocatalytic reactions. In this minireview, we focus on the latest progress of the atomically surficial modulations on two-dimensional (2D) semiconductor photocatalysts and their role in enhancing selectively photocatalytic performance. We hope this minireview could provide with new insights for researchers on nanosynthesis and photocatalysis.